When Risk Becomes Normal: Risk-Normalizing Behavior and Consumer Behavior Deviance in Excessive Consumption - Gilang Mukti Prabowo; Natiq Al Aksar (Jurnal Ekuisci, 2026)
Background. Excessive consumption has increasingly become embedded in everyday consumer life through digital marketplaces, social media trends, installment-based payments, flash sales, and lifestyle-oriented consumption. Aims. Prior studies have discussed maladaptive consumption, compulsive buying, and perceived risk, but have paid limited attention to how consumers reinterpret risk until excessive consumption appears normal. Methods. The research was conducted through a narrative literature review of studies on maladaptive consumption, compulsive buying, perceived risk, behavioral decision-making, social influence, risk normalization, and the normalization of deviance. Relevant literature was identified from peer-reviewed journal articles, theoretical works, and recent studies discussing consumer behavior, overconsumption, and digital consumption. Result. This conceptual paper introduces Risk-Normalizing Behavior as a mechanism explaining how consumption-related risk becomes acceptable, manageable, or worth taking on. Based on the literature on these mechanisms, this paper develops a conceptual framework linking distorted risk perception, risk-normalizing behavior, and consumer behavior deviance. Conclusion. This paper contributes to consumer behavior literature by extending perceived risk from risk evaluation toward risk normalization and by offering Risk-Normalizing Behavior as a conceptual bridge for understanding excessive consumption practices.